2011
DOI: 10.5513/jcea01/12.3.948
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Evaluation of Bread Waste as a Replacement for Maize in the Diet of Growing Snails

Abstract: The effect of replacing maize fraction of the diet of growing snails partially or wholly with bread waste (BW) on performance characteristics and cost benefits was studied for 12 weeks. A total of 120 growing snails (Archachatina marginata) of mean weight 83.67 ± 3.5g of about 3 months of age were randomly allotted to 4 dietary treatments, BW 1 , BW 2 , BW 3 and BW 4 in which maize fraction of the diet was replaced at 0, 50, 75 and 100% with BW respectively, in a completely randomized design replicated 3 times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…It is a possible agro-industrial by-product that can be incorporated into broiler chickens feed as energy source in order to decrease the cost of production. In a study, Omole et al, (2011) assessed the performance and cost benefits of replacing maize fraction of the diet of growing snails (Archachatina marginata) with bread waste and concluded that bread waste meal (BWM) can replace 100% maize fraction of snail diets without any deleterious effect in the performance of the snails. Likewise, Fakunmoju (2014), observed better performance in catfish when their meal was supplemented with BWM.…”
Section: Introductionmentioning
confidence: 99%
“…It is a possible agro-industrial by-product that can be incorporated into broiler chickens feed as energy source in order to decrease the cost of production. In a study, Omole et al, (2011) assessed the performance and cost benefits of replacing maize fraction of the diet of growing snails (Archachatina marginata) with bread waste and concluded that bread waste meal (BWM) can replace 100% maize fraction of snail diets without any deleterious effect in the performance of the snails. Likewise, Fakunmoju (2014), observed better performance in catfish when their meal was supplemented with BWM.…”
Section: Introductionmentioning
confidence: 99%
“…Higher protein content are available in insects when comparing to lean red meat sources of beef (23.2%), veal (24.8%) and mutton (21.5%) (Kinyuru et al, 2011). Although livestock by-products such as chicken offal which consists of 65.8% crude protein are lower prices than fish meals (Omole et al, 2008), this cheap protein sources are lacking of essential biological values of amino acids (Shariff & Mona, 2013). Therefore, B. dubia could be used to replace the meat protein sources as it is easy to maintain in the small area of farm because rearing of this insects are inside the storage boxes that can be piled one above another.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, mild form of constipation was found in the G4 group, where more than 50% bread waste was included in the diet. As bread waste contains less fiber [16] which may cause constipation, and the animals are maintained in confinement, where pigs did not have any access to other sources of fiber. Besides this, the feeding preference of pigs is varied depending on the type of food material.…”
Section: Resultsmentioning
confidence: 99%